Groundwater recharge estimation using chloride mass balance method on the southern slope of Merapi Volcano, Indonesia - Restu Dwi Cahyo Adi; Wahyu Wilopo; Hendy Setiawan (Institute of Advanced Engineering and Science, 2023)
Groundwater is a main resource for the majority of Indonesian people as a source of clean water to meet their daily needs. The increase in groundwater use is unavoidable due to increasing development in Indonesia, especially in Yogyakarta. Groundwater recharge is important in the hydrological cycle to meet groundwater needs. Therefore, this study aims to estimate groundwater recharge by the chloride mass balance (CMB) method on the southern slope of Merapi Volcano in Yogyakarta, Indonesia. This research was conducted in the rainy and dry seasons from August 2022 until January 2023. This research collects annual rainfall near the study area from the Meteorology, Climatology, and Geophysics Agency (BMKG) Yogyakarta station, monthly data collected from eighteen samples of groundwater station, and monthly data collected from fifteen samples of rainwater in the study area. The chemical content of groundwater and rainwater samples is analyzed using argentometry to obtain chloride concentration. The result of annual rainfall in the study area is 3,603.878 mm/year. The average chloride concentration in rainwater is 1.1 mg/L, while the average chloride concentration in groundwater is 8.015 mg/L. The CMB method calculation showed that the recharge in the study area ranges from 171.65 to 1,711.29 mm/year. The groundwater recharge has a positive correlation with elevation and rainfall. High groundwater recharge is also found in the northern area due to fractured lava aquifer.